Agricultural cooperatives in the North-East development region of Romania: Economic perspectives - Krisztina Melinda Dobay (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The role of agricultural cooperatives in supporting farmers has become increasingly important in the context of crises and unforeseen economic fluctuations, helping to improve their position in the value chain. If at the level of the European Union about 34% of farmers are part of agricultural cooperatives, in Romania only 1% are members in associative entities. The data indicate that the largest number of agricultural cooperatives is located in the North-East Region (a quarter of the total), especially in Boto÷sani County. However, analyzing the information on their economic activity, we found that a large part of them either never filed a balance sheet or submitted statements that they did not carry out economic activities. Of those who filed a balance sheet, half declared zero turnover. However, 57 agricultural cooperatives registered a profit for 2020 in the analyzed Region. In this paper, we aimed to identify the most profitable fields of activity for agricultural cooperatives in the North-East Development Region of Romania.
Keywords: Q13; H32; R1; 330; agricultural cooperative; regional analysis; turnover; profit; North-East DevelopmentRegion of Romania